ANALYSIS OF FLOOD DISCHARGE OF THE BLORONG RIVER, KENDAL DISTRICT - Apriarso, Dally; Kusuma, Ilham; udin, Ikhwan; Yudaningrum, Farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2025)
Abstrack. The Blorong River is a river in the Brangsong District, Kendal Regency, Central Java Province, which has the potential to be hit by flood disasters almost every year. So conditions like this can cause losses to communities around the Blorong River. Through the research carried out, the aim was to determine the maximum discharge of the Blorong river with a river length of ± 3.3 km. The calculations and analysis applied in this research use quantitative methods. The primary data taken is documentation of the existing conditions of the Blorong river, while the secondary data is rainfall data from Balai Pusdataru Bodri Kuto. Analysis of the planned flood discharge using the Nakayasu HSS method shows that the planned return period flood discharge is Q2 years = 236,500 m³/s, Q5 years = 276,392 m³/s, Q10 years = 296,294 m³/s and Q25 years = 300,180 m³/s. After comparing it with the results of manual calculations of the existing conditions of the Blorong River using the Manning formula. The solution to the problem of flooding from the Blorong river is to normalize the river, raise the embankment in the STA section which is no longer able to accommodate the planned flood discharge, and also provide regulations so that people do not throw rubbish in the river.Keywords: Flood Analysis, Flood Discharge, Blorong River